2018
DOI: 10.1063/1.5047475
|View full text |Cite
|
Sign up to set email alerts
|

Formation of field-reversed configuration using an in-vessel odd-parity rotating magnetic field antenna in a linear device

Abstract: A Field-Reversed Configuration (FRC) is formed by an in-vessel odd-parity rotating magnetic field (RMF) antenna in a tandem mirror device, Keda mirror with axisymmetricity. The 40-cm diameter antenna is fed independently by four IGBT-based power units with an output current of 1500 A each at 84 kHz, and their phases are adjustable to launch odd or even parity RMFs. A medium-sized washer gun is utilized to generate a highly ionized seed hydrogen plasma. Driven by RMF, the resultant FRC is formed with a separatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Previously, it has been reported that FRCs were formed using RMF current drive [26,27]. Note that, in this experiment, the RMF is used to create azimuthal rotating fluid, instead of forming FRC.…”
Section: Experiments Setupmentioning
confidence: 94%
See 1 more Smart Citation
“…Previously, it has been reported that FRCs were formed using RMF current drive [26,27]. Note that, in this experiment, the RMF is used to create azimuthal rotating fluid, instead of forming FRC.…”
Section: Experiments Setupmentioning
confidence: 94%
“…Hence, a set of new RMF antennas has been installed in the mid-plane of the central cell along with four independently controlled power sources connected to the antenna to create an RMF. Similar to the method we reported earlier [26], the frequency has been tuned at 88 kHz with maximum currents of 1.6 kA, corresponding to 17.6 Gauss on the axis of the device.…”
Section: Experiments Setupmentioning
confidence: 99%
“…A novel method for improving the mirror's axial confinement based on the rotating magnetic field (RMF) scheme has been tested on the KMAX [36]. The idea is to use the RMF to form a closed magnetic field structure [37], that is field reversed configuration (FRC), in the plug cell and the continuing operation of RMF can capture the particles, which will stave off the axial loss from the central cell. A preliminary result shows that there is ∼40% improvement in the confinement.…”
Section: Simulations and Experimentsmentioning
confidence: 99%
“…The experiments were conducted on KMAX-FRC [25]. KMAX θ-pinch FRC is an FRC experiment with θ-pinch coils installed inside the central cell of an axisymmetric tandem mirror device named KMAX [26][27][28]. As depicted in figure 1(a), KMAX has a total length of ∼11 m, which is primarily comprised of one central cell, two side cells, and two end chambers.…”
Section: Keda Mirror With Axisymmetry (Kmax)-frcmentioning
confidence: 99%